The Impact of Reward Systems on Employee Performance in Selected Hotels in Cape Town - Nkouangas, Ludmilla Yvette; Onojaefe, Darlington Peter (Acta Universitatis Danubius. Œconomica, 2023)
Despite the interest shown by scholars, policy, and practitioners in hotel and hospitality's reward systems, relatively little research has been performed on how reward systems might increase motivation and performance. Few studies explored the significance and impact of the reward system on employee performance in the hospitality industry; consequently, it is necessary to investigate the relationship between the reward system and other employment characteristics to solve employee reward discord. This article sought to examine how reward systems impact employee performance, attraction and retention in selected hotels in Cape Town South Africa. Through quantitative techniques, 180 questionnaires were distributed at 12 selected hotels in Cape Town. The Statistical Package for Social Sciences (SPSS) was used to analyse 136 responses using descriptive analysis (frequency tables and mean) and Chi-square test. The results indicated that rewards, performance, attractiveness, and retention were positively correlated. The study concluded that non-financial and financial rewards are vital for both improved employee motivation and changed behaviour in worker’s performance. The research suggested that hotel management reassess their compensation system to improve workers' motivation and performance. This research provide the academics with knowledge regarding the impact of reward systems on employee performance with particular reference to the hotel industry.